PENGARUH PANDEMI COVID-19, VOLUME PERDAGANGAN SAHAM, DAN KAPITALISASI PASAR TERHADAP RETURN SAHAM - Silvianto, Crystalice Stephanie; Hastuti, Rini Tri (Jurnal Paradigma Akuntansi, 2025)
This study was conducted with the aim of knowing and proving whether there is an influence of daily growth in positive Covid-19 confirmed cases, stock trading volume and market capitalization on stock returns contained in the LQ-45 index on the Indonesia Stock Exchange (IDX) starting from February 3, 2020 to January 31, 2022. In this study, it used a non-probability sampling method to determine the sample to be used. This study used 35 samples of companies that had been selected through the criteria specified in this study. In this study, collecting secondary data and the data that has been obtained will be processed using Microsoft Excel and also Eviews software version 10. The results of this study show that the growth of positive daily cases of Covid-19, trading volume and market capitalization negatively affects stock returns.